KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA PEGAWAI DI MAN DONGGALA KABUPATEN DONGGALA - Hikmawati; Masmur M; Darmawansyah (STKIP Subang, 2026)
This study examines the managerial competence of the principal in improvingemployee performance at MAN Donggala, Donggala Regency. The research wasmotivated by the strategic role of school principals in managing educationalresources effectively to enhance the performance of teachers and educational staff.The objective of this study was to analyze the principal’s managerial competenceand its implementation in improving employee performance. This researchemployed a qualitative approach with a descriptive design. Data were collectedthrough observation, interviews, and documentation involving the principal,teachers, educational staff, and students as informants. Data analysis wasconducted through data reduction, data presentation, and conclusion drawing, whiledata validity was ensured through source and technique triangulation. The findingsindicate that the principal’s managerial competence at MAN Donggala has beenimplemented effectively through school planning, organization management,supervision, employee development, and the creation of a disciplined workenvironment. The principal improved employee performance by providing guidance,motivation, coaching, and continuous evaluation. Furthermore, the principalfostered responsibility, cooperation, and discipline among employees, enablingtasks to be carried out effectively and efficiently. The study concludes that strongmanagerial competence contributes significantly to improving employeeperformance and supports the achievement of educational goals and school qualityenhancement.